A culture of masculinity or survival? Gendered perspectives of violence among incarcerated youth - Magnus, Amy M. (Deviant behavior, 2021)
Recent scholarship challenges the notion that the study of men’s and boys’ attitudes toward violence and their participation in violent behavior extends to women and girls. Using data collected from youth within the California Department of Juvenile Justice, this paper builds upon prior scholarship to elucidate women’s and girls’ perceptions of and experiences with violence, and the extent to which they differ from boys’ and men’s in carceral environments. Our analysis suggests that instead of trying to ‘be like boys’, girls recognize the benefit of violence as a means of survival in carceral institutions and will engage in violence if it seems beneficial for their livelihood. This differentiates the strive for masculinity and the need to survive in juvenile institutions, a finding that corroborates what critical, feminist scholars argue are the unique perceptions of, participation in, and experiences of violence among young women.